Global food price pass-through in Sri Lanka: A causality analysis - Sivarajasingham, Selliah (2015)
Food prices have been increasing sharply since 2003 in Sri Lanka as well as in the world.In the globalized world, the transmission of global food price increases to domestic market determines the decision of economic agents and policy makers of a domestic economy.Thus, this study examines how international food price increases affects domestic inflation dynamic process in Sri Lanka. To assess this purpose, the study uses the VAR Granger causality/Block Exogeneity Wald Tests. The empirical statistical results are derived by using parametric and non-parametric econometric techniques.The data span for this study is from 2003M1 to 2013M12.Granger causality reveals unidirectional causal relationship running from global food price to domestic prices and the past changes of global food price help to explain current changes of domestic prices over and above the study period in Sri Lanka.Therefore, Sri Lankan government needs to develop a safety net program for the poor and a longer term poverty reduction strategy.The results of this study have various policy implications for monetary policy, food and agricultural policy and trade policy for Sri Lanka.